What do you think about climate finance? - Stroebel, Johannes; Wurgler, Jeffrey (Journal of Financial Economics, 2021)
We survey 861 finance academics, professionals, and public sector regulators and policy economists about climate finance topics. They identify regulatory risk as the top climate risk to businesses and investors over the next five years, but they view physical risk as the top risk over the next 30 years. By an overwhelming margin, respondents believe that asset prices underestimate climate risks rather than overestimate them. We also tabulate opinions about the expected correlation between growth and climate change, social discount rates appropriate for projects that mitigate the effects of climate change, most influential forces for reducing climate risks, and most important research topics.